Investigando Chlorolobion braunii em escala laboratorial: uma abordagem fisiológica para o entendimento do efeito sinérgico de cobre e LEDs branco/azul/vermelho na síntese de biomoléculas - Bolli, Julia (Universidade Federal de São Carlos, 2023)
Microalgae are photosynthetic microorganisms with extensive biodiversity and physiological plasticity, serving as primary producers in aquatic ecosystems. They play a crucial ecological role by contributing to the balance of the food chain in these environments and maintaining climatic conditions through their biological CO2 mitigation activity. Through physiological and metabolic responses to environmental variations, the biochemical composition of microalgae can be altered, turning algal metabolism into a significant biotechnological tool to optimize biomass production and enhance the synthesis of high-value biomolecules such as lipids, carbohydrates, proteins, and carotenoids. This study aimed to evaluate the effects of the element copper (Cu) and LED lights of white, blue (λ 420-470 nm), and red (λ 660 nm) colors on growth parameters, photosynthetic responses, and biomolecule production of the microalga Chlorolobion braunii. Cultivations were conducted in benchtop photobioreactors, with environmentally relevant copper concentration (5.0x10-7 mol.L-1). Growth parameters were monitored, revealing that higher growth rates were achieved under white and blue light (~ 1.0 d-1) compared to red light (~ 0.75 d-1). Photosynthetic parameters such as maximum and effective quantum yields and photochemical quenching were unaffected by the manipulations, while non-photochemical quenching (NPQ) was higher under white and blue light (~ 0.3) compared to red light (~ 0.2). The hormesis effect was observed in protein production under the combination of red light and additional copper, resulting in a ~ 165% increase in protein content compared to the control under the same light color. Biochemical results demonstrated that copper addition favored biomolecule synthesis, notably oil production, which composed 80% of the dry biomass, suggesting the role of lipids as a preferred energy reserve in Chlorolobion braunii, highlighting it as a promising microalga for the energy sector.
Investigating Chlorolobion braunii on a laboratory scale: a physiological approach to understanding the synergistic effect of copper and white/blue/red LEDs on biomolecule synthesis.
Keywords: Microalgas; Fotossíntese; Biomoléculas; Microalgae; Photosynthesis; Biomolecules; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA